ORIENTALIST COMMUNICATION IN VIEWING THE AUTHENTICITY OF THE QUR'AN - Muhammad Nurul Fadillah (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2022)
Abstrak : Indonesia adheres to the ideology of Pancasila, the first principle of which is divinity. Every citizen is obliged to embrace religion. Islam is the largest religion in Indonesia so it is very necessary to study more about Islam so that Muslims develop their knowledge. One of them is by knowing the problems of Islam, this is the communication of orientalists in viewing the authenticity of the Qur'an. The method used in this research is descriptive literature review, getting data from references and describing the results of the library data obtained. So as to get a conclusion from the formulation of the problem of the views of orientalists on the authenticity of the Qur'an, and the response of scholars to the views of orientalists on the authenticity of the Qur'an.